New Trends in Teacher's Education. Educational Placement of the Adopted Child. (12th February 2015) - Novara, Cinzia; Garro, Maria; Serio, Consuelo; Vitrano, Simona
Abstract: In Italy, the number of adopted school-age children is increasing. According to the Commission of Intercountry Adoption (2013), 3106 children were adopted, 47.5% of them are between 5 and 9 years old. The present action-research aims at exploring the spread of good approaches in schools in terms of welcoming of adopted children. For this purpose, 268 teachers of primary schools were involved in analyzing the social representation about adopted children and their family. The results show a simplified vision of the adoptive family, which is described as heroic family or, on the contrary, as a family with difficulty.